Random amplified polymorphic DNA analysis of Campylobacter jejuni and Campylobacter coli isolated from healthy cattle and sheep - Açik, MN; Çetinkaya, B (Microbiology Soc, 2006)
The genetic heterogeneity among Campylobacter jejuni and Campylobacter coli isolates obtained from apparently healthy cattle and sheep was investigated by random amplified polymorphic DNA (RAPD) analysis. A total of 348 Campylobacter isolates, consisting of C. jejuni (n = 218) and C. coli (n = 130), were analysed. All these isolates were successfully typed by RAPID analysis. The total numbers of band patterns defined by RAPID in cattle and sheep were 42 and 45, respectively. Of the 42 distinct types obtained from cattle, 37 types were observed in C. jejuni isolates (n = 115), and the remaining 5 were in C. coli isolates (n = 30). Of 45 distinct types obtained from sheep, 21 types were observed in C. jejuni isolates (n = 103), and 24 were in C. coli isolates (n = 100). It was concluded that a high degree of heterogeneity existed among the C. jejuni and C. coli isolates of healthy cattle and sheep.
Keywords: Poultry; Food; Rapd; Pcr